Prasangka dan Konstruksi Seksualitas LGBT dalam Majalah Al-Wa’ie Online - Syaifullah Syaifullah (Living Islam: Journal of Islamic Discourses, 2018)
Law No. 39, 1999 Chapter 3 guarantees people’s protection of human rights. However, in fact, discriminations still exist in social life. LGBT is one of the objects of discrimination by many parties. Media is an example. The presence of media influences people’s  preconception. This study investigates al-Wa’ie’, an online magazine, focusing on it’s prejudice and sexuality construction of LGBT. This study is of literature review with discourse analysis method. The data is analyzed using Baron and Byrne’s theory of prejudice and theory of sexuality construction. The results of the study indicated that there were prejudices on online al-Wa’ie’ Magazine of LGBT, that consisted of: first, cogni- tive component, i.e. a stereotyping of LGBT as criminals, perverted-minded, and harmed the value of humanity; second, affective component, i.e. the use of negative words as well as the urge to exterminate LGBT; third, conative component, i.e. hostility and discrimination toward LGBT. The sexuality construction on online al-Wa’ie’ Magazine.